Tris(2-chlorobenzyl)(1H-1,2,4-triazole-5-thiolato-kappa S)tin(IV)-tris(2-chlorobenzyl)(4H-1,2,4-triazole-3-thiolato-kappa S) tin(IV) (1/1) - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
Tris(2-chlorobenzyl) tin hydroxide condenses with 3-mercapto-1,2,4-triazole to form the 1:1 cocrystal of the title compound, [Sn(C(7)H(6)Cl)(3)(C(2)H(2)N(3)S)]. The asymmetric unit contains two molecules which differ only in the position of the nitrogen-bound H atom of the triazole ring; one molecule is linked to the other molecule by an N-H center dot center dot center dot N hydrogen bond. In the second molecule, two of the chlorobenzyl units are disordered over two positions in a 0.73 (1):0.27 (1) ratio. The Sn atom in both molecules shows a distorted tetrahedral SnSC(3) coordination.